Efficacy and safety of PD-1 and PD-L1 inhibitors in advanced colorectal cancer: a meta-analysis of randomized controlled trials - Zhenzi Wang; Yuan Liu; Kedi Wang; Liyan Ma (BMC Gastroenterology)
Abstract Background PD-1 and PD-L1 inhibitors have emerged as promising therapies for advanced colorectal cancer (CRC), but their efficacy and safety profiles require further evaluation. This meta-analysis aims to assess the efficacy and safety of PD-1/PD-L1 inhibitors in this patient population. Methods A systematic review and meta-analysis were conducted following PRISMA guidelines, with data sourced from PubMed, Embase, CENTRAL, Web of Science, and CNKI up to August 3, 2024. Nine randomized controlled trials (RCTs) involving 1680 patients were included. The primary outcomes were overall survival (OS), progression-free survival (PFS) and objective response rate (ORR), while safety was assessed through adverse events (AEs) and grade ≥ 3 AEs. Effect sizes were calculated using mean differences (MD) and risk ratios (RR) with 95% confidence intervals (CIs). Results Overall, the meta-analysis showed that PD-1/PD-L1 inhibitors did not significantly extend OS (MD = 0.86, 95% CI: -0.55, 2.27), but they significantly improved PFS (MD = 2.53, 95% CI: 0.92, 4.15). Additionally, PD-1/PD-L1 inhibitors did not significantly increase the ORR compared to controls (RR = 1.19, 95% CI: 0.99, 1.44). In terms of safety, PD-1/PD-L1 inhibitors did not significantly increase the incidence of overall AEs. Subgroup analysis further indicated that PD-1 inhibitors significantly improved OS (MD = 1.24, 95% CI: 0.20, 2.29) and PFS (MD = 6.27, 95% CI: 0.56, 11.97), while PD-L1 inhibitors did not have a significant impact on these outcomes. Additionally, PD-L1 inhibitors were associated with a higher risk of grade ≥ 3 AEs (RR = 1.29, 95% CI: 1.07, 1.57), a risk not observed with PD-1 inhibitors. Conclusion PD-1 inhibitors significantly improve PFS and OS in advanced CRC, making them a preferable option over PD-L1 inhibitors, which show limited efficacy and a higher risk of severe AEs. These findings support prioritizing PD-1 inhibitors in clinical practice for this patient group, while caution is warranted with PD-L1 inhibitors due to their safety concerns. Trial registration PROSPERO (CRD42024611696).